Rural Works Programme - Planning Commission (Planning Commission, 1964)
One of the major objectives of the Third Five Year Plan is "to utilize to the fullest possible extent the manpower resources of the country and to ensure a substantial expansion in employment opportunities". Two new programmes of great importance for the expansion of employment opportunities in rural areas have been initiated in the Third Plan, namely, the "Rural Works Programme" and the "Rural Industries Projects". The details of the Rural Works Programme are set out in the note which has been printed in this brochure along with the connected papers and circulars. The programme provides for labour-intensive works meant to increase agricultural production and create community assets and these will be in addition to the programmes included in the Slate and local Plans. Special provision is made in the Central budget for meeting the entire expenditure on the programme in the form of 50 per cent loan and 50 per cent grant to be given to the State Governments.
Planning Commission Government of India New Delhi February 1964